1998
DOI: 10.1159/000020851
|View full text |Cite
|
Sign up to set email alerts
|

First-Trimester Multifetal Pregnancy Reduction: Evaluation of Technical Aspects and Risks from 2,756 Cases in the Literature

Abstract: Objective: To evaluate the technical aspects, efficacy and safety of first-trimester multifetal pregnancy reduction in the management of multifetal pregnancies, an analysis of the international literature on first-trimester multifetal pregnancy reduction was made. Materials: Thirty-three studies were selected from an international review of the literature. Total fetal loss rate, risk of fetal loss after the procedure with the different techniques and gestational age at delivery were the main parameters studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…However, studies that have focused on loss rates per gestational sac or embryo, not per patient, observed that the rates of spontaneous fetal demise in multiple gestations during early pregnancy were much lower than those reported by other studies that did not consider this condition (29-31). Moreover, reported rates of malformation after MFPR are lower than expected rates, which is probably due to the tendency to selectively reduce embryos with a higher risk of congenital malformation (12). Several studies reported that MFPR during early gestation, at 7-8 weeks, without KCl injection showed superior results to that performed later (13, 16).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, studies that have focused on loss rates per gestational sac or embryo, not per patient, observed that the rates of spontaneous fetal demise in multiple gestations during early pregnancy were much lower than those reported by other studies that did not consider this condition (29-31). Moreover, reported rates of malformation after MFPR are lower than expected rates, which is probably due to the tendency to selectively reduce embryos with a higher risk of congenital malformation (12). Several studies reported that MFPR during early gestation, at 7-8 weeks, without KCl injection showed superior results to that performed later (13, 16).…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have been conducted on different routes of approach, and shown controversial results (12, 15, 32). Experience and skill are also important factors in addition to the route of approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite some ethical concerns, multifetal reduction in high‐order multiple pregnancies is widely accepted as a procedure that does more good than harm. Many previous studies have shown that multifetal reduction in high‐order multiple pregnancies can improve pregnancy outcomes . For twin pregnancy, which accounts for the vast majority of multiple pregnancies after ART, pregnancy outcomes are far from as good as those of singletons.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that multifetal reduction of high‐order multiple pregnancies results in improved pregnancy outcomes . However, whether conducting elective fetal reduction from dichorionic twins after IVF is worthwhile remains controversial.…”
Section: Introductionmentioning
confidence: 99%